Measurement of the top-quark mass in tt̄ + 1-jet events collected with the ATLAS detector in pp collisions at √s = 8 TeV - Aaboud, Morad; Anders, Christoph; Andrei, George Victor; Antel, Claire; Bolz, Arthur; Brandt, Oleg; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Geisler, Manuel Patrice; Helary, Louis; Jongmanns, Jan; et al. (Journal of high energy physics, 2019)
A determination of the top-quark mass is presented using 20.2 fb-1 of 8 TeV proton-proton collision data produced by the Large Hadron Collider and collected by the ATLAS experiment. The normalised differential cross section of top-quark pair production in association with an energetic jet is measured in the lepton+jets final state and unfolded to parton and particle levels. The unfolded distribution at parton level can be described using next-to-leading-order QCD predictions in terms of either the top-quark pole mass or the running mass as defined in the (modified) minimal subtraction scheme. A comparison between the experimental distribution and the theoretical prediction allows the top-quark mass to be extracted in the two schemes. The value obtained for the pole-mass scheme is: rnirle 171.1 0.4 (stat) 0.9 (syst) 173 (theo) GeV. The extracted value in the running-mass scheme is: rnt(rnt) = 162.9 0.5 (stat) 1.0 (syst) 1:12 (theo) GeV. The results for the top -quark mass using the two schemes are consistent, when translated from one scheme to the other.
The ATLAS Collaboration: M. Aaboud, C.F. Anders, V. Andrei, C. Antel, A.E. Bolz, O. Brandt, M. Dunford, D.E. Ferreira de Lima, S. Franchino, M.P. Geisler, L. Helary, J. Jongmanns, M. Klassen, M. Kolb, A. Krishnan, A. Kugel, M. Lisovyi, H. Meyer zu Theenhausen, F. Napolitano, D.I. Narrias Villar, M. Sahinsoy, A. Schöning, H.-C. Schultz-Coulon, T.M. Spieker, R. Stamen, P. Starovoitov, S. Suchek, J. Wang, S.M. Weber, M. Wessels, X. Yue und 2895 weitere
Gesehen am 09.04.2020
s steht im Titel unter dem Wurzelzeichen